Admissibility of Estimated Regression Coefficients Under Generalized Balanced Loss - Luo, J.; Qiu, H.-B.; Zhang, Jiajia (Ukrains’kyi Matematychnyi Zhurnal, 2015)
There are some discussions concerning the admissibility of estimated regression coefficients under the balanced loss function in the general linear model. We study this issue for the generalized linear regression model. First, we propose a generalized weighted balance loss function for the generalized linear model. For the proposed loss function, we study sufficient and necessary conditions for the admissibility of the estimated regression coefficients in two interesting linear estimation classes.